2009
DOI: 10.1007/s11356-009-0123-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of 353-nonylphenol and its metabolites for zebrafish embryos

Abstract: We have noticed that in our article published in the ESPR-March issue [Environ Sci Pollut Res 16(2):227−231 (2009)] the first name of the last author is wrong. "Andreas" Telscher has to be replaced by Markus Telscher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The 24‐h NOEC of BPA for all sublethal endpoints in zebrafish embryos is 2.0 mg/L . The NOEC of NP for nonlethal malformations in zebrafish embryos is from 1 mg/L to 2.5 mg/L . Consistent with previous studies, our results showed that the exposure did not significantly affect the hatching and survival rates of embryos or larvae.…”
Section: Discussionsupporting
confidence: 91%
“…The 24‐h NOEC of BPA for all sublethal endpoints in zebrafish embryos is 2.0 mg/L . The NOEC of NP for nonlethal malformations in zebrafish embryos is from 1 mg/L to 2.5 mg/L . Consistent with previous studies, our results showed that the exposure did not significantly affect the hatching and survival rates of embryos or larvae.…”
Section: Discussionsupporting
confidence: 91%
“…It can be determined in short examinations prior to experiments. To distinguish already low contaminant effects from background mortality, we propose a correspondingly low spontaneous lethality rate (≤2.5%), which is in line with the results from Kammann et al [40,41]. In comparison, the OECD recommends to discard datasets with a lethality equal or above 10% under control conditions [18,19].…”
Section: Recommendations For the Use Of Microinjections As Tool In Tosupporting
confidence: 54%
“…For the example of the FET, a binary four-parameter logistic model (see Fig. 1a and Appendix) has been found suitable [27][28][29]. The EC xx concept does not rely on using the logistic model; it can be adapted to every other strictly monotone concentration-response model.…”
Section: Resultsmentioning
confidence: 99%